The effectiveness of incidental physical activity interventions compared to other interventions in the management of people with low back pain: A systematic review and meta-analysis of randomised controlled trials. (March 2019) - Alzahrani, Hosam; Mackey, Martin; Stamatakis, Emmanuel; Pinheiro, Marina B.; Wicks, Manuela; Shirley, Debra
Abstract: Objectives: To investigate the effectiveness of incidental (non-structured) physical activity interventions for the management of people with low back pain (LBP). Design: Systematic review and meta-analyses of randomised controlled trials. Setting: Eligible published trials from the earliest date available to November 2017. Participants: People with non-specific LBP aged 18 years or over. Outcome measures: Pain, disability and physical activity-related outcomes. Results: Three trials were included (including a total of 422 participants). The quality of trials, assessed by PEDro scale, was high (7 out of 10). For pain, the pooled results did not show any significant effects between the incidental physical activity intervention and other interventions at any time point. For disability, incidental physical activity was not statistically more effective than other interventions at short-term; however, the pooled results favoured incidental physical activity at intermediate-term (weighted mean difference (WMD) = -6.05, 95%CI: -10.39 to −1.71) and long-term (WMD = −6.40 95%CI: -11.68 to −1.12) follow-ups among participants with chronic LBP. The overall quality of evidence was rated "moderate-quality" based on the GRADE system. Conclusions: The incidental physical activity intervention provided improvement in disability in intermediate- and long-term for people with chronic LBP, although this improvement was small and may not be clinically significant. Highlights: Incidental physical activity intervention provided improvement in disability in intermediate- and long-term. Incidental physical activity intervention was not more effective than other interventions for pain. Incidental physical activity intervention offer another option for those who find it hard to adhere to exercise programs. Further research is needed on incidental physical activity as an intervention for LBP, particularly, in inactive people.